Exploring dimensions of brand personality for Generation Y in the apparel market: The case of Turkey - ÇOBANOĞLU, EMİNE (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2015)
Successful apparel brand management calls for crafting brand imagery, such as brand personality, around the apparel brand. Building a brand personality around the apparel brand is one way to form an attachment between consumers and the brands they choose to wear on the grounds of self-identification. The aim of this study is to explore the applicability of Aaker's (1997) brand personality dimensions to apparel brands for Generation Y in Turkey, one third of whose population belongs to this generation. Generation Y consumers posit a profitable target market for apparel brands, based on the size of the group and its apparel consumption. The findings of the study confirm the widely accepted brand personality dimensions of sincerity, excitement, competence and sophistication. Ruggedness, on the other hand, was not extracted, probably due Generation Y's postmodern way of life. The study found a new apparel brand personality dimension, uniqueness, which might be elaborated in detail in future studies. Another dimension that appeared in this study was traditionalism, which confirmed previous brand personality studies in Turkey. Implications for apparel brand managers are provided in terms of how to communicate their brand personality alternatives to Generation Y through conducting various marketing mix activities.
Keywords: brand personality; Generation Y; apparel; brand positioning; uniqueness